2014
DOI: 10.1016/j.stem.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3a and Dnmt3b Have Overlapping and Distinct Functions in Hematopoietic Stem Cells

Abstract: SUMMARY Hematopoietic stem cells (HSCs) are the precursors of the hematopoietic system responsible for the lifelong production of blood and bone marrow. Given the emerging importance of epigenetic regulation in HSC fate decisions and malignant transformation, we investigated the role of the DNA methyltransferase Dnmt3b through genetic ablation in HSCs – either alone or in combinatorial deletion with its paralog Dnmt3a. While conditional inactivation of Dnmt3b alone in adult HSCs had minor functional impact, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
268
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(291 citation statements)
references
References 40 publications
(59 reference statements)
16
268
0
1
Order By: Relevance
“…To determine the impact of DNA methylation changes on gene expression, promoter DNA methylation levels of the differentially expressed genes were examined. Similar to our previous studies (16,19), gene expression changes between control and Dnmt3a KO T-ALL were not associated with consistent DNA methylation differences ( Figure 3c). …”
Section: Dnmt3a Ko Nicd+ T-all Exhibits a Gene Expression Profile Ressupporting
confidence: 89%
See 1 more Smart Citation
“…To determine the impact of DNA methylation changes on gene expression, promoter DNA methylation levels of the differentially expressed genes were examined. Similar to our previous studies (16,19), gene expression changes between control and Dnmt3a KO T-ALL were not associated with consistent DNA methylation differences ( Figure 3c). …”
Section: Dnmt3a Ko Nicd+ T-all Exhibits a Gene Expression Profile Ressupporting
confidence: 89%
“…In addition crucial roles for Dnmt3a in HSC differentiation (16,19) and myeloid tumor suppression (21,35), the studies presented here establish important functions for Dnmt3a in T-cell development and evolving T-ALL. While activating NOTCH1 mutations are the major genetic lesion in T-ALL (7), little progress has been made into developing targeted therapies for these patients, likely due to the context of how co-operating mutations shape the leukemia biology.…”
Section: Discussionmentioning
confidence: 52%
“…More extensive analysis in vivo using hematopoietic tissuespecific conditional Dnmt3a-deleted animals revealed progressive expansion of long-term HSC compartment with impaired differentiation in Dnmt3a-null cells by incomplete epigenetic repression of HSC-specific genes [28]. More recently, hematopoietic tissue-specific conditional loss of both Dnmt3a and Dnmt3b resulted in enhanced HSC self-renewal and a more severe differentiation block than Dnmt3a single-null cells, partly due to activated β-catenin signaling [29]. In agreement with the murine data, recent targeted deep sequencing study has identified recurrent DNMT3A mutations at high allele frequency in highly purified HSC population as well as in normal T-cell compartment in AML patients [10].…”
Section: Dnmt3amentioning
confidence: 99%
“…12 Conditional deletion of DNMT3A in murine HSC causes a higher self-renewal capacity and reduced differentiation resulting in an accumulation of HSC in the bone marrow. 10,13 In two studies, patients with DNMT3A mutations had higher survival rates when treated with high-dose daunorubicin (90 mg/m…”
Section: Dnmt3amentioning
confidence: 99%